An introduction to neighborhood sustainability assessment tool (NSAT) study for China from comprehensive analysis of eight Asian tools - Cheshmehzangi, Ali; Dawodu, Ayotunde; Song, Wangyang; Shi, Yuzhu; Wang, Yuwei (2020)
In comparison to city-level and building-level sustainability research, neighborhood-level sustainable urban development is less studied. One of the ways of achieving sustainability at this level is the use of the Neighborhood Sustainability Assessment Tool (NSAT), which focuses on the sustainable urban development of districts, communities, and neighborhoods. NSAT is comprised of urban sustainable indicators and associated points ascribed towards achieving specific urban agendas, called headline sustainability indicators (HSIs) and themes. In China, neighborhood-level sustainability agenda has just been recently established in 2017. Hence, there is an immediate need for NSAT development of multiple cities responding to specific regions of different climate zones in China. As an example, this study utilizes the case of Ningbo City, located in east China, for such NSAT development. This paper provides a comprehensive analytical and comparison study of eight Asian NSATs to highlight compatibilities and extract specific indicators for a new NSAT development for China. The results from this comparative and analytical study, developed through a multidimensional approach of sustainable pathway model (SPM) inform a new NSAT development in a new context. This novel contribution is significant in a context where neighborhood sustainability measures are recently developed. This study serves as the starting point for future research of NSATs in China and other countries.